Circulating markers of inflammation and infection as adjuncts to a clinical scoring system in predicting outcome in cancer patients with febrile neutropenia - luyanda.kwofie@nhls.ac.za (University of Pretoria, 2013)
Dissertation (MSc (Immunology))--University of Pretoria, 2010.